Comparison of self-report and objective measures of male sexual dysfunction in a Japanese primary care setting: a cross-sectional, self-administered mixed methods survey. Issue 1 (22nd January 2021) - Takeuchi, Yuki; Otsuka, Ryohei; Kojima, Hajime; Fetters, Michael D
Abstract : Objectives: Erectile dysfunction (ED) is a common problem among middle-aged males and men often do not talk about sexual problems with their primary care physicians (PCPs). We hypothesised that many Japanese men who meet the criteria for ED would not recognise their condition based on responses to an internationally validated scale. Our secondary aims were to examine potential barriers to seeking treatment for ED by their PCPs. We sought to elucidate their perspectives about male sexual dysfunction qualitatively. Through merging of the quantitative and qualitative findings, we sought an enhanced understanding of the factors affecting sexual dysfunction treatment. Design: A cross-sectional, self-administered mixed methods survey was distributed at a suburban family medicine clinic in Sapporo, Japan. Eligible participants were 40 to 69-year-old men who came for routine scheduled visits from 5 November to 21 December 2018. During the office visit, participants completed a confidential 11-item survey addressing sexual dysfunction including the 5-item version of the International Index of Erectile Function scale and open-ended questioning. Setting: Teine Family Medicine Clinic, a suburban family medicine clinic in Sapporo, Japan. Participants: We enroled 66 male patients aged 40–69 years who presented for routine outpatient care in the Teine Family Medicine Clinic. Results: Of surveyed participants, 39% (26/66) reported having sexual dysfunction, but 92% (61/66) met ED criteria. Of respondents, 48% (16/33) had desire for treatment, but only one man had discussed sexual dysfunction with his PCP. Among the 12 desiring treatment from PCPs, the main barriers to discussing were shame (n=7) and lack of awareness that PCPs can treat ED (n=5). These men's perspectives about sexual dysfunction included viewing sexual dysfunction as normal ageing, attributing sexual dysfunction to decreased libido, considering sexual activity for a healthy life, having good rapport with PCPs, having incomplete knowledge about treatment and lacking an intimate relationship. Through a resulting model, the merged mixed methods findings illustrate how patient perceptions can reinforce or attenuate issues of awareness, desire for treatment and barriers to access. Conclusions: In a Japanese primary care setting, the majority of participating male patients met ED criteria on an internationally validated measure, namely, the five-item version of the International Index of Erectile Function, but many were not aware of their ED. Misperceptions, lack of knowledge and personal factors are barriers to treatment. The mixed methods findings suggest misperceptions and personal attributes reinforce or attenuate awareness, preference for treatment and barriers to access. We conclude PCPs should routinely inquire about sexual dysfunction of men at risk and offer treatment to men who would benefit.